Pendekatan Efektif untuk Meningkatkan Pemahaman Matematika pada Siswa di Sekolah Dasar - Nahri, Zulfah (Maliki Interdisciplinary Journal, 2024)
For children, mathematics is very important because it is an important component of education from elementary school to college. A unique method is needed to increase students’ understanding and enthusiasm for mathematics in elementary schools. Using interactive learning techniques such as project-based learning and educational games is one strategy. These techniques can help students understand mathematical ideas more clearly and specifically. Additionally, it is important to use differentiation strategies that take into account individual variations in learning style and pace. to ensure that every student can fulfill his or her potential. Technology, such as math apps and learning software, can also be a useful tool for increasing the relevance and enjoyment of learning. Teaching mathematics in elementary schools is predicted to be more efficient, enjoyable, and of course will improve children’s understanding. As a result, the future academic growth of students will be reasonable.